(untitled) (Research, Society and Development, 2020)
The aim of this work was to evaluate the physical attributes of an Oxisol under grasses in a long-term experiment in Brejo Paraibano. The experiment was installed in an experimental area of ​​the Center for Agricultural Sciences, in the city of Areia-PB. The experimental design was in randomized blocks, with five treatments plus an additional one, and with four replications: T1-Brachiaria decumbens (BD), T2-Brachiaria brizantha (BB), T3-Brachiaria humidicola (BH), T4-Brachiaria brizantha MG5 cv Vitória (BBMG5), T5-Brachiaria ruziziensis (BR) and Native forest (MT), as a reference of the soil’s natural condition. Undisturbed soil samples from the 0-10, 10-20 and 20-30 cm layers were collected in the center of each plot to determine the following attributes: total porosity (PT), Microporosity (Mi), macroporosity (Ma), soil aeration capacity(SAC), bulk density (Bd), degree of compaction (DC), field capacity (θFC), permanent wilt point (θPWP), available water (θAW), in addition to soil resistance to penetration in field (PR). It is concluded that fourteen years after implantation there was a significant difference in the surface layer between treatments for the attributes of total porosity, microporosity, field capacity, available water and soil aeration capacity. The native forest treatment showed the highest values ​​of total porosity and microporosity in the 0-10 cm layer. Among the grasses, a small variation in the physical attributes of the soil was observed. Regarding available water, significant values ​​were observed in the Brachiaria brizantha treatment in the 0-10 cm layer.